State-Enabled Crimes - Hamilton, Rebecca J. (2016)
They call it basat al-reeh (flying carpet). It is a custom-built wooden cross with a hinge in the middle. As Syrian survivors describe it, those torturing the survivors would tie them down on the cross, then force the two halves of the cross together, crushing the detainee inside. Basat al-reeh has been used systematically across state-run detention sites throughout Syria, with instructions on its use disseminated through the state apparatus and information on the implementation of those instructions sent back through a multi-nodal chain of command